Medical consultation system for community clinics in remote area - Talukder, Md. Fuad Hassan; Yeasmin, Farzana (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.